Faktor-faktor yang melatarbelakangi keputusan perempuan untuk bertahan dalam abusive dating relationship - Sintyasari, Ni Luh Dwi; Fridari, I Gusti Ayu Diah (Jurnal Psikologi Udayana, 2021)
Dating is a process of exploration and investigation of individuals in an intimate relationship. Having a relationship has a positive impact, but also has negative effects, one of which is abusive dating relationship. In an abusive dating relationship, women can choose to leave or stay in the relationship. A women’s decision to stay on the relationship caused by various factors. This research aimed to discover factors behind women’s decision to stay in abusive dating, utilizing a qualitative approach with a case study method. The sampling method used in this research is purposive sampling method. The respondents on this research were three women aged 21-23 years old who have been dating for more than one year and are staying in the abusive dating relationship. The results showed that commitment, cognitive bias, social support, relationship satisfaction, and positive reinforcement were factors behind women’s decision to stay on abusive dating relationship.